Evaluation of multiple reactions in dilute benzoyl peroxide concentrations with additives using calorimetric technology. (March 2021) - Huang, An-Chi; Huang, Chung-Fu; Tang, Yan; Xing, Zhi-Xiang; Jiang, Jun-Cheng
Abstract: Benzoyl peroxide (BPO) is a typical organic peroxide widely used in food processing, particularly flour bleaching. Due to the unstable nature of the oxygen-oxygen bond in BPO, it readily reacts under even mid-low-temperature conditions. Lower concentrations of BPO are also potentially explosive, even when combined with acid or alkaline additives. Given the history of both potential and documented industrial accidents, this study investigates the thermal stability of various BPO concentrations when mixed with acid or alkaline solutions. In addition, differential and integral kinetic models were applied to verify that the apparent activation energy data from the differential scanning calorimetry experiments were valid. The results of autocatalysis reactions and n th-order reaction simulations presented characteristics consistent with the experimental findings. The findings in this paper can be used as a reference for BPO products that are mediated with either an acid or an alkaline solution during production, storage, transportation, or use. Highlights: The thermal hazards of low-concentration BPO mixed with different additives were examined. Safety parameters calculated using different methods were compared. The SADT values of low-concentration BPO with additives in different storage tanks were determined. Calorimetry technology was used to evaluate and expound the thermal stability of low-concentration BPO with additives.